1983
DOI: 10.1136/bmj.287.6391.517
|View full text |Cite
|
Sign up to set email alerts
|

Serum selenium concentration related to myocardial infarction and fatty acid content of serum lipids.

Abstract: A longitudinal case-control study of 33 patients with one or more risk factors for coronary heart disease and 64 controls showed that the serum selenium concentration (range 0-63-1 33 ,umol/l [tg/l)) was not associated with development of clinical manifestations of coronary heart disease during a follow up of five to seven years. The content of polyunsaturated fatty acids, especially eicosapentaenoic acid, in serum cholesterol esters and phospholipids was positively correlated with selenium concentration.As a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…In several prospective (3)(4)(5) and case-control (6) studies, low serum selenium levels were associated with increased risk of coronary heart disease. However, in other studies, this association could not be confirmed (7)(8)(9)(10). Antioxidant defense is achieved by additive or synergistic action of enzymes and antiox-idant nutrients (11,12).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…In several prospective (3)(4)(5) and case-control (6) studies, low serum selenium levels were associated with increased risk of coronary heart disease. However, in other studies, this association could not be confirmed (7)(8)(9)(10). Antioxidant defense is achieved by additive or synergistic action of enzymes and antiox-idant nutrients (11,12).…”
mentioning
confidence: 93%
“…The question of whether low selenium status predisposes to cardiovascular disease has been addressed in a number of studies in the past decade (3)(4)(5)(6)(7)(8)(9)(10). In several prospective (3)(4)(5) and case-control (6) studies, low serum selenium levels were associated with increased risk of coronary heart disease.…”
mentioning
confidence: 99%
“…Feeding was conducted daily for 10 weeks. An additional 2 weeks of behavioral testing was conducted after BSSG feeding ended (total 12 weeks of testing) to allow blood sterol content to become normalized (Sanders et al 2000;Miettinen et al 1983). At this stage, half the mice were sacrificed.…”
Section: Feeding Of Bssgmentioning
confidence: 99%
“…It was reported that approximately 60% of selenium in plasma is present as selenoprotein P (Satia et al, 2005;Stranges et al, 2006). This protein differs from other selenoproteins in that it incorporates up to 10 Se atoms per molecule in the form of selenocysteine as opposed to the single selenocysteine incorporated in other selenoproteins (Miettinen et al, 1983). Selenoprotein P is abundant throughout the body suggesting that one function is to serve as a primary transporter in systemic selenium delivery (Rayman, 2000;2005).…”
Section: Ajesmentioning
confidence: 99%